2023
DOI: 10.1186/s40104-023-00851-2
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol alleviates oxidative stress induced by oxidized soybean oil and improves gut function via changing gut microbiota in weaned piglets

Abstract: Background Oxidized soybean oil (OSO) has been shown to impair growth and exacerbate inflammation, leading to intestinal barrier injury in animals. Recent evidence suggests important roles for resveratrol (RES) in the promoting growth performance, antioxidant capacity, anti-inflammatory, and regulate intestinal barriers in animals. Therefore, The objectives of this study are to investigate the effects of dietary RES (purity 98%) supplementation on the growth performance, antioxidant capacity, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 80 publications
2
4
0
Order By: Relevance
“…In this study, we found that Res dramatically improved the mRNA level of Nrf2 and elevated the antioxidant CAT expression after OSO was challenged. These results are similar to those of Gao’s study, in which Res mitigated jejunal damage in weaned piglet exposure to OSO by elevating the mRNA of antioxidant enzymes …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, we found that Res dramatically improved the mRNA level of Nrf2 and elevated the antioxidant CAT expression after OSO was challenged. These results are similar to those of Gao’s study, in which Res mitigated jejunal damage in weaned piglet exposure to OSO by elevating the mRNA of antioxidant enzymes …”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to those of Gao's study, in which Res mitigated jejunal damage in weaned piglet exposure to OSO by elevating the mRNA of antioxidant enzymes. 28 Oxidative stress damages the intestinal barrier function by various mechanisms. 67 For example, the increase in oxidative stress is inextricably linked to the intestinal inflammatory response.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Piglet feces were put into sealed plastic bags, treated with 10% sulfuric acid for nitrogen fixation, and immediately stored in a −20 • C refrigerator until testing. The contents of total energy (GE), crude protein (CP), crude fiber (CF), crude fat (EE) and organic matter (OM) in the feces and diets were determined, and the nutrient digestibility of each nutrient was calculated [16].…”
Section: Growth Performance and Nutrient Digestibilitymentioning
confidence: 99%
“…In order to mitigate the adverse effects of weaning, supplementation with plant extracts has been shown to constitute an effective strategy for alleviating stress and enhancing growth performance in animals[ 10 , 11 ]. Isoflavones, a type of flavonoid mainly found in legumes, have been reported to assuage oxidative stress in broilers[ 12 ], finishing pigs[ 13 ], and lactating sows[ 14 ], improve the intestinal health of newborn and weaned piglets[ 15 , 16 ], and enhance the immunity of broilers treated with lipopolysaccharide or virus[ 17 , 18 ], thereby playing a crucial protective role in animal production.…”
Section: Introductionmentioning
confidence: 99%